What do we know about creatine supplementation? - Egierska, Dominika; Perszke, Michał (Journal of Education, Health and Sport, 2022)
Creatine is one of the most often used supplements nowadays. Its popularity can be attributed to a wide variety of clinical implications. The intent of this paper was to evaluate and review the latest publications about the usage and potential clinical effects on the human body of creatine supplementation and to bring attention to new findings in this subject. Authors explored PubMed, CrossRef and Google Scholar using keywords: creatine, supplements, ergogenic aids, neuroprotection, bioenergetics. Furthermore, the references of selected articles were manually investigated for additional relevant articles. The bibliography focused mainly on systematic reviews, randomized controlled trials (RCTs) and case reports. The selection of individual articles was carried out in accordance with the determinants of general medicine readership. There is still a lot to learn about creatine supplementation and its potentially beneficial effects. Further evidence-based studies are required, as the amount of reliable data and information is still not sufficient and lots of them have yet to be examined.